SOCIAL MEDIA FOR SUSTAINABLE KNOWLEDGE SHARING: IMPACT ON LIFESTYLES AND AWARENESS - KAUR, Amandeep (Asian Education and Learning Review, 2025)
This study explores the role of social media in fostering behavioral changes towards knowledge sharing related to sustainability and healthier lifestyles. Recognizing the potential of e-media for knowledge dissemination, innovation, and creativity, the research investigates how social media can drive the automated habit formation of knowledge sharing. Adopting a theoretical approach with content analysis, the study examines user behavior, challenges in habit formation, and strategies for optimizing knowledge sharing. Through a thorough literature review, the study assesses the impact of e-media on sustaining healthier lives and promoting planetary well-being. Findings emphasize the need for cultivating inner connection and awareness to optimize creative and innovative knowledge sharing. Ultimately, the study aims to better understand how social media can be harnessed to promote sustainable lifestyles and increased awareness, thereby contributing to a healthier, more responsible global community.